Is Low‐Temperature Fission‐Track Annealing in Apatite a Thermally Controlled Process?. (17th March 2020) - Tamer, Murat; Ketcham, Richard
Abstract: We report a new series of experiments to explore the phenomenon of low‐temperature annealing of fission tracks in apatite that feature a number of improvements over previous work. Grain mounts were preirradiated using 252 Cf to increase confined track detection and allow briefer thermal neutron irradiation. We coirradiated and etched four apatite varieties (Durango, Fish Canyon, Renfrew, and Tioga) over five time steps equally spaced from 3.66 to 15 ln(s). A length standard was coetched with all experiments to ensure that subtle differences are within detection limits. Finally, we used a standard etching protocol, allowing the data to be comodeled with extensive high‐temperature data sets and recent analyses of induced tracks that underwent ambient‐temperature annealing over year‐to‐decade time scales. Ambient‐temperature annealing occurs at two different rates, with faster annealing at early stages that decreases to a slower rate that converges with empirical fanning linear or curvilinear models. The nature of this decrease varies among the apatite species examined, but no patterns could be determined. The fitted models make geological time‐scale predictions consistent with those based on high‐temperature data only and also make predictions consistent with reasonable inferred low‐temperature histories for all four apatite varieties. The empirical fanning curvilinear equation encompasses low‐temperature annealing at month‐to‐decade time scales, but low‐temperature annealing at shorter time scales may occur by a distinct mechanism. We consider but rule out annealing by radiation from short‐lived activated isotopes. We also reconsider the notion of the initial track length, and the appropriate length for normalizing confined track length measurements. Plain Language Summary: We present a new series of experiments to study the extent to which the radiation damage from fission decay of uranium in the mineral apatite is annealed (healed) at room temperature. We combine data obtained by etching fission tracks seconds after being generated in a nuclear reactor with tracks etched minutes, hours, days, months, years, and even decades after generation and find that detectable annealing occurs over these time spans. We combine these data with previous experiments conducted at high temperatures to see whether the model equations currently used to describe high‐temperature annealing can encompass the low‐temperature data, which would support the idea that the same atomic‐scale processes control both. We find that most of our low‐temperature data are consistent with the high‐temperature data and model equations, with the exception of earliest‐stage experiments that show faster‐than‐expected annealing, possibly caused by a different process. We consider but reject a possible annealing effect from secondary radiation. These data make it clear that a truly "unannealed" track length is unmeasurable, which in turn requires that we reconsider how we normalize measurements of annealed lengths. Our measurements also allow us to more confidently characterize fission‐track annealing at earth‐surface conditions over geological time scales. Key Points: We document apatite fission‐track annealing at Earth‐surface conditions in the seconds to decades after track formation Empirical annealing equations encompass most low‐ and high‐temperature experimental data, indicating that the same processes control both There is evidence of a distinct annealing process operating during the seconds after induced track formation